Assessing Statistical Anxiety Among Online and Traditional Students - Frey-Clark, Marta; Natesan, Prathiba; O’Bryant, Monique (Frontiers in Psychology, 2019)
The purpose of this study was to determine whether scores on the modified two-factor Statistical Anxiety Scale (SAS) manifest in the same way for students in online and traditional statistics courses. Tests of measurement invariance indicated that invariance of the two-factor model of the SAS held at every level. Therefore, we compared the statistical anxiety of online and traditional students. Results indicated that online and traditional statistics students reported comparable levels of anxiety with slightly less anxiety in terms of seeking help for traditional students. We concluded that online instruction is a viable form of statistics education at least for undergraduate students enrolled in the social sciences.